2013
DOI: 10.5607/en.2013.22.3.143
|View full text |Cite
|
Sign up to set email alerts
|

Brain-Region Specific Apoptosis Triggered by Eph/ephrin Signaling

Abstract: Eph receptors and their ligands, ephrins, are abundantly expressed in neuroepithelial cells of the early embryonic brain. Overstimulation of Eph signaling in vivo increases apoptotic cell death of neuroepithelial cells, whereas null mutation of the Eph gene leads to the development of a larger brain during embryogenesis. Thus, it appears that Eph-ephrin signaling plays a role in regulating apoptotic cell death of neuroepithelial cells, thereby influencing brain size during embryonic development. Interestingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Although it was postulated that fusion of neural folds at the midline is mediated by an adhesive interaction between EphA7 and ephrin-A5, an alternative explanation is that a significant increase in the dorsal midline cell population may be responsible for the neural tube closure defects in ephrin-A5 null mutant embryos. Consistent with this hypothesis, recent studies using in vivo expression of ephrinA5-Fc or EphA8-Fc revealed that upregulation of Eph/ephrin signaling in the dorsal midline play a causative role in triggering massive apoptotic cell death ( Kim et al, 2013 ; Park et al, 2013 ). These findings suggest that cell-cell contact in a brain region where Eph and ephrin are co-expressed triggers the pro-apoptotic signaling pathway downstream of the Eph-ephrin complex, a critical mechanism for modulating the size of the neuroepithelial cell population or remodeling brain tissue ( Park, 2013 ).…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Although it was postulated that fusion of neural folds at the midline is mediated by an adhesive interaction between EphA7 and ephrin-A5, an alternative explanation is that a significant increase in the dorsal midline cell population may be responsible for the neural tube closure defects in ephrin-A5 null mutant embryos. Consistent with this hypothesis, recent studies using in vivo expression of ephrinA5-Fc or EphA8-Fc revealed that upregulation of Eph/ephrin signaling in the dorsal midline play a causative role in triggering massive apoptotic cell death ( Kim et al, 2013 ; Park et al, 2013 ). These findings suggest that cell-cell contact in a brain region where Eph and ephrin are co-expressed triggers the pro-apoptotic signaling pathway downstream of the Eph-ephrin complex, a critical mechanism for modulating the size of the neuroepithelial cell population or remodeling brain tissue ( Park, 2013 ).…”
Section: Introductionmentioning
confidence: 63%
“…Consistent with this hypothesis, recent studies using in vivo expression of ephrinA5-Fc or EphA8-Fc revealed that upregulation of Eph/ephrin signaling in the dorsal midline play a causative role in triggering massive apoptotic cell death ( Kim et al, 2013 ; Park et al, 2013 ). These findings suggest that cell-cell contact in a brain region where Eph and ephrin are co-expressed triggers the pro-apoptotic signaling pathway downstream of the Eph-ephrin complex, a critical mechanism for modulating the size of the neuroepithelial cell population or remodeling brain tissue ( Park, 2013 ). Although the pro-apoptotic pathway downstream of the Eph/ephrin complex has not been clearly elucidated, a recent study suggested that EphA receptors may cross-talk with cell death receptors such as tumor necrosis factor receptor 1 (TNFR1) ( Lee et al, 2013 ).…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Expression studies using Eph-Fc or ephrin-Fc fusion proteins reveal that the developing embryo is subdivided into domains demarcated by reciprocal and mutually exclusive expressions of Eph receptors and its corresponding ligands and ephrins ( Gale et al, 1996 ; Park, 2013 ; Park et al, 2013 ). For example, EphA receptors are predominantly expressed in the dorsal region of the diencephalon and anterior mesencephalon, whereas ephrin-A ligands express in the posterior mesencephalon.…”
Section: Introductionmentioning
confidence: 99%